The Role of the Judiciary in Interpreting the Doctrine of ‘Locus Standi’ in Environmental Pollution in Nigeria - Ngwu Godwin Emeka Ph.D; Chioma Nnajiofor Blessing LL.B, BL; Maureen Obiageli Ugwu Esq., LLB (Hons), BL (Hons), LL.M (Law and Economy, 2023)
Locus Standi being a vital aspect in law has gained controversies in recent times amongst legal authorities and the public generally. This is apparently because of the discrepancies in judicial pronouncements, confusion and complexities of the conceptual crises which had engulfed the doctrine and its application by Nigerian courts. The doctrine of locus standi had been misunderstood and misapplied by the courts in Nigeria, which had blindly followed Adesanya’s case in the interpretation of the doctrine by including the provisions of section 6 (6) (b) of the 1999 Constitution of the Federal Republic of Nigeria (as amended). Hence, this work examines the role of the judicial arm of government with respect to interpretation of the “locus standi” in environmental pollution in Nigeria and also incorporates the test to determine “locus standi”. This paper equally hoped to contribute to both learning and also serves as a good source of example to the society at large, and also putting forward recommendations primarily for the adoption of as opposed to its strict and restrictive system in line with best practices. The paper was concluded by stating that this belief will advance the legal system thereby delimiting the restriction on access to court and the efficient dispensation of justice.